Epigenetic Changes Associated With Interleukin-10 - Zheng, Zhonghua; Huang, Gang; Gao, Tong; Huang, Tianyi; Zou, Mengsha; Zou, Yuhao; Duan, Shiwei (Frontiers in Immunology, 2020)
Abstract IL-10 is a regulator of inflammation and immunosuppression. IL-10 regulates a variety of immune cells to limit and stop the inflammatory response, and thus plays an important role in autoimmune diseases, inflammatory diseases and cancer. IL-10 is closely related to epigenetic modification, in which changes in DNA methylation of IL10 gene can affect mRNA and protein levels of IL10. In addition, changes in histone modifications, especially histone acetylation, can also lead to abnormal expression of IL10 mRNA. At the same time, a handful of IL-10 related microRNAs (miRNAs) are found to be aberrantly expressed in multiple diseases. Besides, long noncoding RNA (lncRNA) growth arrest specific transcript 5 (GAS5) also inhibits IL-10 expression. Here, we reviewed the epigenetic changes related to IL-10 in various diseases, as well as the regulation of IL-10 gene expression in various diseases by epigenetic modifications such as DNA methylation, histone modification, miRNA, and lncRNA.